elearning Strategies to Enhance Eye Care Training - Chia Wei Ling, Audrey; Loh, Kai-Lyn; Xiangrong, Bryan Sim; Lim, Eunice; Lim, Siew Leng; Jayabaskar, Thiyagarajan (International Journal of Advanced Corporate Learning (iJAC), 2025)
Myopia prevalence in Asia remains among the highest globally, accompanied by widespread misconceptions about its management. For eye care practitioners, staying updated on emerging research and debunking myths is critical to delivering effective patient care. However, traditional approaches to professional development, such as in-person workshops or online modules, often fail to account for the time constraints and demanding schedules of practitioners. Effective learning strategies must go beyond mere knowledge delivery to address the behavioral and motivational challenges that impact the application of knowledge in real-world settings. This paper explores an award-winning eLearning initiative by the Singapore National Eye Centre designed to advance professional development in basic myopia management. By leveraging innovative online learning strategies, this project equips practitioners with evidence-based insights while fostering meaningful behavioral change. The program’s design aligns with the evolving demands of healthcare education, emphasizing practical application, adaptability, and outcomes-driven learning. In the context of a rapidly changing healthcare landscape, this initiative demonstrates how well-structured eLearning can empower practitioners to navigate complex research, dispel prevalent myths, and ultimately improve patient care.